Control Of the Distribution and Consumption of Alcoholic Beverages in the City of Medan - Yusuf Nugraha, Rafli; Sarihati, Tati; Santosa, Pandji (Journal of Indonesian Rural and Regional Government, 2025)
The control of alcohol distribution and consumption in Medan City is part of the local government's efforts to maintain social order and public health. This study aims to evaluate the effectiveness of policy implementation based on Hasibuan’s (2016) theory, which includes four stages: setting performance standards, measuring actual performance, comparing results with standards, and taking corrective actions. In addition, Nugroho’s (2018) policy control theory is used to examine aspects of monitoring, evaluation, and law enforcement. The findings indicate that control efforts have been carried out through enforcement operations, public education, and minor criminal court proceedings (tipiring). However, challenges such as illegal distribution via COD systems, limited resources, and low public awareness remain significant obstacles. Policy evaluation has not yet fully adapted to technological developments and new distribution patterns. Therefore, regulatory revisions, strengthened intersectoral coordination, and improved institutional capacity are needed to ensure more effective and sustainable alcohol control.